Convertible manganese contrast for molecular and cellular MRI - Shapiro, Erik M. (2008)
We describe here the use of inorganic manganese based particles as convertible MRI agents. As has been demonstrated with iron oxide particles, manganese oxide and manganese carbonate particles can be internalized within phagocytotic cells, being subsequently shuttled to endosomes and/or lysosomes. As intact particles, only susceptibility induced MRI contrast is exhibited, most often see as dark contrast in susceptibility weighted images. Modulation of MRI contrast is accomplished by the selective degradation of these particles within the endosomal and lysosomal compartments of cells. Upon particle deconstruction in the endosomes and lysosomes, the dissolved Mn(2+) acts as a T(1) agent, eliciting bright contrast in T(1) weighted images. This modulation of MRI contrast is demonstrated both in vitro in cells in culture, and also in vivo, in rat brain. These particles are the potential building blocks for an entire class of new environmentally responsive MRI contrast agents.